2017
DOI: 10.1111/joim.12586
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality after hip fracture in elderly persons from Europe and the USA: the CHANCES project

Abstract: In this large population-based sample of older persons across eight cohorts, hip fracture was associated with excess short- and long-term all-cause mortality in both sexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
164
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(193 citation statements)
references
References 38 publications
12
164
0
5
Order By: Relevance
“…The physiologic stress of hip fracture may render these individuals more susceptible to complications of and demise from common comorbid conditions compared with individuals with more robust physiologic reserves. Three studies, including a recent meta‐analysis across eight cohorts, have reported the association of hip fracture with early incident mortality to be indeed stronger among those with a higher burden of pre‐fracture comorbid illness . The findings of Andrich and colleagues are also consistent with the hypothesis that pre‐fracture reduced functional status may also be an effect modifier of the association between major osteoporotic fractures and mortality.…”
Section: Early Post‐fracture Mortality: the Case Of Pelvis Fracturesmentioning
confidence: 76%
“…The physiologic stress of hip fracture may render these individuals more susceptible to complications of and demise from common comorbid conditions compared with individuals with more robust physiologic reserves. Three studies, including a recent meta‐analysis across eight cohorts, have reported the association of hip fracture with early incident mortality to be indeed stronger among those with a higher burden of pre‐fracture comorbid illness . The findings of Andrich and colleagues are also consistent with the hypothesis that pre‐fracture reduced functional status may also be an effect modifier of the association between major osteoporotic fractures and mortality.…”
Section: Early Post‐fracture Mortality: the Case Of Pelvis Fracturesmentioning
confidence: 76%
“…Roughly 1 in 2 white women and 1 in 5 men are predicted to have an osteoporosis‐related fracture in their lifetime in the US . As the population ages, the risk of fractures in the advanced age group, which is associated with high morbidity and mortality rate, should increase . Therefore, it is important to establish noninvasive therapy to promote healing of compromised fracture repair in long bones and vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of women in the USA, the incidence of any clinical fracture at 1 and 2 years following the initial fracture was 10% and 18%, respectively [26], but the corresponding figures for women ≥ 75 years of age were higher, with a 2-year fracture risk of 25%. All-cause mortality is also highest in the year following a hip fracture [5, 10, 23, 27, 28]. …”
Section: Introductionmentioning
confidence: 99%